2018
DOI: 10.1016/j.clnesp.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition therapy for critically ill patients across the Asia–Pacific and Middle East regions: A consensus statement

Abstract: The objective of the Working Group in formulating these statements is to guide healthcare professionals in practicing appropriate clinical nutrition in the ICU, with a focus on improving quality of care, which will translate into improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 54 publications
0
31
0
3
Order By: Relevance
“…To our knowledge, there is one other published study showing that protein targets can be achieved with a VHPF, although the formula was based on hydrolyzed protein [ 25 ]. It has been suggested that a predigested formula may potentially be beneficial in improving tolerance [ 24 ], but data are lacking to support this hypothesis, and nutritional guidelines recommend the use of polymeric formulas in critically ill patients [ 11 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is one other published study showing that protein targets can be achieved with a VHPF, although the formula was based on hydrolyzed protein [ 25 ]. It has been suggested that a predigested formula may potentially be beneficial in improving tolerance [ 24 ], but data are lacking to support this hypothesis, and nutritional guidelines recommend the use of polymeric formulas in critically ill patients [ 11 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Park et al, the presence of a nutritional support team had a positive and significant effect on the nutritional and clinical outcomes of ICU patients [48]. Evidence suggests that using these guidelines and nutritional protocols can help increase nutritional adequacy and prevent complications arising from inappropriate nutrition in ICU patients [50][51][52]. ICU patients are a heterogeneous group, and in order to meet their nutritional needs, a single approach cannot be used for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Это особенно важно для больных с ОРДС на ИВЛ, так как микроаспирации вследствие нарушения пассажа химу- Науковий огляд / Scientific Review са или нарушения технологии энтерального питания сопряжены с возникновением аспирационных пневмоний и ухудшением респираторной функции. Сывороточные и растительные белки -это «быстрые» некоагулируемые белки, которые быстрее перевариваются и усваиваются, чем казеин, как «медленный» белок [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: положение на животеunclassified
“…- Науковий огляд / Scientific Review мией [12,13]. Несколько ретроспективных и небольших проспективных исследований показали, что ЭП во время положения лежа на животе не увеличивает риск возникновения желудочно-кишечных или легочных осложнений, поэтому мы рекомендуем пациенту, для которого требуется положение лежа на животе, получать раннее ЭП [14].…”
Section: рекомендация 5 выбор смесиunclassified